Effect of extended aging on calpain-1 and -2 activity in beef longissimus lumborum and semimembranosus muscles. (September 2017) - Colle, M.J.; Doumit, M.E.
Abstract: Our objectives were to (Exp. 1) determine the effect of postmortem aging (2, 3, 4, 14, 28, and 42 days) on calpain-1 and -2 activity in beef longissimus lumborum (LL) and semimembranosus (SM) steaks and (Exp. 2) determine the effect of postmortem aging for two extended periods (63 and 84 days) on calpain-2 activity of beef SM steaks. Calpain-1 was not active in either muscle following 14 days of aging. Native calpain-2 activity decreased ( P < 0.001) with longer aging periods for both the LL and SM in Exp. 1 and for the SM in Exp. 2. Autolyzed calpain-2 activity increased ( P < 0.001) with longer aging for the LL and SM in Exp. 1 and for the SM in Exp. 2. Our results indicate that both calpain-1 and calpain-2 may contribute to the postmortem improvement of beef tenderness, with calpain-1 being responsible for the tenderness improvement early postmortem and calpain-2 responsible for additional tenderization during extended aging.